2015
DOI: 10.1097/dbp.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Anatomic Consequences of Diabetic Pregnancy on Memory in Ten-Year-Old Children

Abstract: Objective Pregnancies complicated by diabetes mellitus impair offspring memory functions during infancy and early childhood. The purpose of this study was to investigate the long term consequences of such pregnancies on memory and memory-related brain regions in 10-year-old children. Method Nineteen (19) children of diabetic mothers (CDMs) and thirty-five (35) children of non-diabetic mothers participated in this 10 year follow-up study. Memory performance was assessed using a continuous recognition memory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
0
22
2
Order By: Relevance
“…In vivo structural neuroimaging provides a noninvasive methodology for investigating neuronal volume indirectly via gray matter volume quantification (Pohlack et al, ). Prior studies have used structural MRI to measure hippocampal volume in pediatric populations (Barnea‐Goraly et al, ; Bauer et al, ; Hershey et al, ; Jabès et al, ; Mestre et al, ; Plessen et al, ) and found reduced hippocampal volume in children with diabetes and metabolic syndrome (Bruehl, Sweat, Tirsi, Shah, & Convit, ; Yau, Castro, Tagani, Tsui, & Convit, ). Here, we used structural MRI methods to examine the effects of prenatal exposure to maternal obesity on hippocampal volume in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo structural neuroimaging provides a noninvasive methodology for investigating neuronal volume indirectly via gray matter volume quantification (Pohlack et al, ). Prior studies have used structural MRI to measure hippocampal volume in pediatric populations (Barnea‐Goraly et al, ; Bauer et al, ; Hershey et al, ; Jabès et al, ; Mestre et al, ; Plessen et al, ) and found reduced hippocampal volume in children with diabetes and metabolic syndrome (Bruehl, Sweat, Tirsi, Shah, & Convit, ; Yau, Castro, Tagani, Tsui, & Convit, ). Here, we used structural MRI methods to examine the effects of prenatal exposure to maternal obesity on hippocampal volume in children.…”
Section: Discussionmentioning
confidence: 99%
“…The linear regression models were unadjusted models (Model 1), and models adjusting for ICV (Model 2), ICV and child age (Model 3), and with additional adjustments for SES and exposure to maternal GDM (Model 4), and additionally, child BMI z ‐score (Model 5). These covariates were previously shown to influence hippocampal volume and thus were added to the model to control for potential confounding (Bauer et al, ; Hair, Hanson, Wolfe, & Pollak, ; Jabès, Thomas, Langworthy, Georgieff, & Nelson, ; Krogsrud et al, ; Mestre et al, ; Uematsu et al, ). Since the majority (93%) of children were prepubertal (Tanner stage < 2), Tanner stage was not adjusted in the regression models.…”
Section: Methodsmentioning
confidence: 99%
“…In other rodent models of GDM, where pregnant rats were treated with Streptozotocin to induce betacell toxicity, GDM-exposed offspring had reduced CA1 and CA3 neuronal density compared to unexposed offspring, which further suggests that the GDM prenatal environment adversely affects hippocampal structure, particularly the CA1 and CA3 subfields (Golalipour, Kafshgiri, & Ghafari, 2012;Lotfi, Hami, Hosseini, Haghir, & Haghir, 2016). However, the limited evidence from a single human study did not find a significant relationship between hippocampal volume and prenatal GDM-exposure in 10-year-old children (Jabès, Thomas, Langworthy, Georgieff, & Nelson, 2015). This apparent discrepancy may be attributed to the lack of granularity typically afforded by in vivo volumetric neuroimaging studies.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities of electroencephalography (EEG) patterns were reported in infants of diabetic mothers compared to infants of control mothers (Castro Conde et al, 2013; Jabes et al, 2015; Deregnier et al, 2000). From birth to one year of age, two studies described EEG patterns of newborns or infants born to diabetic mothers compared to infants born to control mothers.…”
Section: Introductionmentioning
confidence: 99%